2009
DOI: 10.3168/jds.2009-2491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidoreduction potential and of gas bubbling on rheological properties and microstructure of acid skim milk gels acidified with glucono-δ-lactone

Abstract: Milk oxidoreduction potential was modified using gases during the production of a model dairy product and its effect on gel setting was studied. Acidification by glucono-delta-lactone was used to examine the physicochemistry of gelation and to avoid variations due to microorganisms sensitive to oxidoreduction potential. Four conditions of oxidoreduction potential were applied to milk: milk was gassed with air, nongassed, gassed with N(2), or gassed with N(2)H(2). The rheological properties and microstructure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…3c, d). The obtained results were in agreement with the findings of Martin et al (2009) who reported that G 0 and G 00 of GDL-induced skim milk gels increased in the 0.016-1.60 Hz range.…”
Section: Size Distribution Of Casein Micellessupporting
confidence: 83%
“…3c, d). The obtained results were in agreement with the findings of Martin et al (2009) who reported that G 0 and G 00 of GDL-induced skim milk gels increased in the 0.016-1.60 Hz range.…”
Section: Size Distribution Of Casein Micellessupporting
confidence: 83%
“…So, for GDL-gels, the viscosity was affected by bubbling. Martin et al [20] showed that the type of gas used for bubbling has a significant influence but no clear trend can be deduced from these results in terms of the influence of an oxidizing or reducing environment.…”
Section: Effect Of Eh On a Model Acid Skim Milk Gelmentioning
confidence: 97%
“…Martin et al [20] studied the effects of Eh on model acidified skim milk gels obtained using GDL and prepared under different gaseous conditions. The milk prepared in air is an oxidizing medium; nitrogen, which is a neutral gas, can be used to remove oxygen from milk -even so the milk Eh remains oxidizing in these conditions -and hydrogen leads to a reducing Eh (below 0).…”
Section: Effect Of Eh On a Model Acid Skim Milk Gelmentioning
confidence: 99%
See 2 more Smart Citations